Impact Of Covid 19 On Micro, Small And Medium Self Financed Businesses Among Single Mothers In Sapele Metropolis - Akelemor Edith Ejiro Boye (International Journal of Economics Development Research (IJEDR), 2023)
The MSME Survival Fund was expected to assist the private sector in broadening the country's economy, with an emphasis on women in particular. Understanding how the MSME survival fund programme affects the mechanisms can be exploited to ensure the long-term viability of small and medium businesses is critical. This investigated the impact of COVID-19 on small and medium self-financed businesses among single mothers in Sapele Metropolis as well as the effectiveness of MSMEs survival fund in ameliorating the effect of COVID-19 on MSMEs business. 256 singles mothers were sample for the study multistage sampling procedure which comprises of stratified random sampling technique, purposive sampling technique and accidental sampling technique. The stratified sampling technique was used to sample 8 major communities in Sapele Metroplis. Accidental sampling was used to select 32 single mothers that own MSMEs from each of the communities. The study adopted a validated questionnaire titled “impact of COVID-19 on MSMEs business with a reliability index of 0.87. The data was analysed using mean, standard deviation, percentage, and Chi Square were used in analysing the data in SPSS version 25. The study found that COVID-19 caused unprecedented reduction in business contract; reduction in access to products/raw materials; reduction in production capacity; reduction in delivery of goods and services; and reduction in sales volume. 18.14% and 25.00% of the single mothers who own self-financed MSMEs accessed the MSMEs survival grant and loan respectively. COVId-19 had a negative strong impact on business operations while MSMEs survival fund had no significant impact on the revitalizations of Business operations of Single mother entrepreneurs. It was critical recommendations among others that Government should make preparations for occurrences like COVID-19, which are likely to have a negative impact on organisations.